Investigation of correlation between mothers’ marital satisfaction and depression among their adolescent in Shiraz - Dastgheib, zahra; Ghobadi Dashdebi, kamel; Gharlipour Gharghani, zabihollah; Hoseini, fatemeh; Babaei Heydarabadi, akbar; Ashrafi Hafez, asghar (Advances in Nursing & Midwifery, 2015)
Abstract Introduction: Depression is the most prevalent malady of the century. About 20 per cent of adolescents between 13 and 19 experience at least a fit of depression before 18. The present study investigated the relationship between mothers’ marital satisfaction and depression among their adolescents in Shiraz, Iran. Materials and Methods: A correlational study was carried out on 300 teenagers of 14-19 years old (160 females and 140 males) and their mothers in educational year of 2009-10, whom were randomly selected among a pool of students from Shiraz’s four Educational Districts. A depression questionnaire with 21 items and a questionnaire of marital satisfaction with 47 items helped in collection of data. Pearson’s correlation of coefficients, regression, and independent t-tests helped in data analysis. Findings: The current study found depression among teenagers as 43.4 per cent and their mothers’ marital satisfaction as 19.2 per cent. We found an inverse significant relationship between marital satisfaction and adolescent depression in both genders (P<0.00d1), with mothers’ marital satisfaction accounting for 0.52 per cent of depression among their teenagers. There was a difference between male and female teenagers in their depression scores (P<0.05). There was also a negative significant relationship between teenagers’ depression and mother’s education and family economic status. Conclusion: Our findings underscored the importance of educational programs intended to prevent depression among teenagers. Keywords: Marital Satisfaction, Depression, Adolescents REFERENCES Anderia A)2002 (College student and depression pilot initiative. National Mental Health Assocation. 24 (30): 4-5. Ahadi B (2002) Marital satisfaction of parents expressing emotions and emotional problems - child behavior. Journal of Psychology. 8 (1): 13-7. (Persian). Atkinson R (2001). Hilgard Psychology. Translated by Rafiee H, et al. Tehran, Arjmand, (Persian). Burns D (1989). Cognitive Therapy for Depression. Translated by Qaracheh Daghi M. Tehran: khatam, (Persian). Butler (2002) Depressive disorder. American Family Physician . 65 (7): 1393-1396. Bakhshi H, Asadpour M, khodadadi Zadeh A) 2007) [Sexual satisfaction in couples with depression. Journal of Qazvin University of Medical Sciences. 11 (2): 37-43. (Persian). Carily S, Pataki MD (2000) Mood disorders and suicide in children and adolescents. In: Comprehensive Textbook of Psychiatry. 6th ed. Philadelphia: Williams & Wilkins. Elizabeth B. Weller MD, Ronald A, et al (2004) Mood disorders in prepubertal children and adolescents. In: Wiener D, editor. Textbook of Child and Adolescent Psychiatry. 3rd ed. USA: The American Psychiatric Pulishing. Goldberg DP, Williams P (1989). The User Guide to General Health Questionnaire. Windsor: Nelson Guilder M (2002) Psychology at Oxford. Translated by Rajabi, M. and others. Tehran, Andisheye rafie Havtvn C, Salkvvys C (2007) Cognitive Behavioral Therapy. Practical manual of mental disorders (translation: i. Ghasem-Zadeh). tehran, Publications arjmand. Jacqueline B (1998). Children healthy lillness and family influences. In: Pitts M, eitor. The psychology of health. London: Rontledge. Jeremy D, Jewel Ph, Keven D, Stark Ph)2003) Comparing the family environments of adolescent with conduct or depression. Journal of Child and Family Studies. 12 (1): 77-89. Kuroshnia M, Latifian M (2007). Study of the relationship of family communication patterns with anxiety and depression in children. Journal of Family Research. 3 (10):587-600. (Persian). Lavar D (2002) Late life depression. Geriatrics.51 (2): 198-210. Mazloomy SS Mirzaei A Mohammadi S (2009). [Study of depression prevalence in the patients with types diabetes reffering to Yazd diabetes researches center in 2008] The Journal of Toloo-e-Behdasht. 7 (1-2) 30- 6. (Persian). Mohammadi D Ghorabi B) (2007) [Behavioral disorders associated with emotional intelligence in students]. Journal of Kerman University of Medical Sciences. 14 (4): 289-299. (Persian). Pinarulu I, Fisiloghlu H (2002). The relationship between Turkish children’s perceptions of marital onflict and their internalizing and externalizing problems. International Journal of Psychology. 37 (6) 369-378. 1393 راهب ،84 هرامش ،24 هرود / 24 ناراکمه و بیغتسد ارهز Rice F Harold G Shelton K Thapar A (2006) Family conflict interacts with genetic liability in predicting childhood and adolescence depression. Journal of the American Academy of Child and Adolescent Psychiatry. 45 (7) 841-848. Rostami M,Yonesi j Sajadi H,Sedghi N (2013). 6th International Congress on Child and Adolescent Psychiatry. (Persian). Sayadi Anari AR. (2002). [Ageing issues in Iran and the world].1rst Edition,Tehran, Publications Ashena. (Persian). Saroukhani M . (2006). Introduction to Sociology of the Family. Seventh Edition,Tehran: Soroush Publications. (Persian). Soltanifar, A. Mehdinia. (2007) [ Prevalence of depressive symptoms in children 9 to 11 years old Tehran and its relationship with the family]. Journal of Mental Health. 9 (39-40) 7-14. (Persian). Taheri S, Nawabi C.[ Study of women 50-18 years old attitudes towards women’s issues in Zanjan]. A summary of a number of research projects and dissertations, Research Zanjan University of Medical Sciences. 2001 - 2002; 114. (Persian). Warner V, Wejssman MM. (1999) Grand parents, parents, and grand children, at high risk for pression. Journal of the American Academy of Child and Adolescent Psychiaty38 (3) 289-96. Wang L, Crane R. (2001) The relationship between marital Satisfaction, Marital stability, nuclear family triangulation, and childhood depression. The American Journal of Family Therapy. 29 (4) 337-347. Weller EB, Weller RA, Rowan AB, Wratch S. (2002) Depressive Disorders in children. In: Lewis M, editor. Child and Adolescent Psychiatry: Acomprehensive Textbook. 3rd ed. Philadelphia, Williarns & Wilkins. Zimmer KP, Minkovitz CS. (2003) Maternal depression: an old problem that merits increased recognition by child health care practitioners. Current Opinion in Pediatrics.15 (6) 636-40. Zahir Aldini AR, Hosseini M, Semnani Y (2004)[ Prevalence of depression and its related factors in high school students of Firouzkouh]. Pejouhandeh. 9 (1) 61-64. (Persian).